Exploring the therapeutic potential and nutritional properties of ’karuppu kavuni’ variety rice of Tamil nadu - HEMAMALINI.S; DR.S.UMAMAHESWARI; DR.R.LAVANYA; DR. C. UMAMAHESWARA REDDY (International Journal of Pharma and Bio Sciences, 2018)
Kavuni rice was considered to be best nutrition supplement since 400BC as it cures gastritis, peptic ulcer and also enhances blood circulation and strengthens the body. The target of this study is to reveal the other therapeutic properties of Karuppu Kavuni arisi through phytochemical screening and in-vitro assay. Karuppu Kavuni was extracted using Ethanol and the crude extract was analysed using GC-MS technique to determine its constituents. Antioxidant assay was carried out by Nitric oxide radical scavenging method and reducing power assay. Arthritic activity was also performed by Egg albumin denaturation method and inhibition of α-amylase and α-glucosidase activity was carried out to determine the Anti-diabetic potential of the rice. The percentage inhibition of the extract was found to be higher in 1000µg/ml compared to other concentration from the in-vitro assays. Therefore, it is reflected as the best Antioxidant, which is Anti-diabetic, reduces inflammation and prevents Arthritis.